A checklist of mammals of Nepal - S. Thapa (Journal of Threatened Taxa, 2014)
A review of the literature on the mammals of Nepal revealed a series of checklists improving in accuracy over time. However, there are contradictions in these checklists and there has been no checklist published since 1975. Here, I present a checklist based on a review of the literature on the mammals of Nepal. The Mammals of Nepal comprise 192 species within 37 families in 12 orders.